Experimental Study of DQPSK Modulation on SDR Platform - Eko Marpanaji; Bamba Riyanto Trilaksono; Armein Z. R. Langi; Adit Kurniawan; Andri Mahendra; Thay Liung (LPPM ITB, 2007)
This Paper addresses Differential Quadriphase Shift Keying (DQPSK) modulation implemented on SDR platform for the development of digital data communications based on Software-Defined Radio (SDR). DQPSK modulation performance perceived at Packet Error Rate (PER) is evaluated in terms of Eb/No or S/N ratio, carrier frequency, bit rate, gain, roll-off factor of root Nyquist filter or root raised cosine filter, and payload size from delivered data. Based on these results, the smallest PER could be obtained by setting Eb/No value greater than 20 dB, carrier frequency of at least 0,3 MHz, optimum bit rate of 200 kbps, optimum range payload size of 2000 up to 4000 bytes, and roll-off factor of Nyquist or root-raised cosine filter of 0.4.